2013
DOI: 10.4174/jkss.2013.85.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Pinch-off syndrome

Abstract: Subclavian venous catheterization was previously frequently performed, but because of life-threatening complications such as hemothorax, pneumothorax, mediastinal hematoma, and myocardial injury, its use has become less common. However, this practice has some advantages in patient mobility, secured dressing, and rapidity and adequacy of vascular access. In some situations where patient comfort is an especially important consideration, such as with totally implantable venous port insertion for chemotherapy, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…4 However, access via puncture of the subclavian vein will always involve risk of a specific complication, known as pinch-off syndrome, which is caused by the catheter being subjected to a pincer movement between the clavicle and the first rib, with consequent partial or total fracture of the catheter. [7][8][9] A systematic review of catheters implanted via the subclavian vein demonstrated that damage to the catheter with microruptures may be more common than is realized and that it may be related to the type of material utilized. 10 Although all TICs have similar shapes, there are specific differences in the choice of materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, access via puncture of the subclavian vein will always involve risk of a specific complication, known as pinch-off syndrome, which is caused by the catheter being subjected to a pincer movement between the clavicle and the first rib, with consequent partial or total fracture of the catheter. [7][8][9] A systematic review of catheters implanted via the subclavian vein demonstrated that damage to the catheter with microruptures may be more common than is realized and that it may be related to the type of material utilized. 10 Although all TICs have similar shapes, there are specific differences in the choice of materials.…”
Section: Discussionmentioning
confidence: 99%
“…In the cases described here, although it is not possible to definitively state the causes, pinch-off syndrome is a probable candidate for the fractures, but there is no obvious explanation for the total detachment. [7][8][9] Constant follow-up of all patients over the long term could lead to development of protocols that indicate which accesses and types of catheter are most appropriate, in order to minimize complications or provide specific prophylaxis for each type of complication.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of portacath fructure is unknown, the impingement of the port catheter between the first rib and the clavicle by surrounding musculoskeletal system was thought by many authors as a possible cause, known as "pinch off syndrome" or thoracic inlet syndrome. (1,(16)(17)(18)(19)(20). It was also supposed that factors such as venous flow, negative inspiratory pressure in the thoracic cavity, changes in thoracic pressure with coughing and vomiting, vigorous movement of the upper arms, neck flexion, were thought to lead to migration of fractured material (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…These two sites of structural weakness are quite different from pinch-off syndrome and are demonstrated in Figure 4. 16,17 The former are located in the neighborhood of the pocket area and the latter is located in a more distal portion of the catheter, just beneath the middle third of the clavicle. Manufacturers have previously attempted to wrap cover material over the locking nut and turn the connecting tube, the catheter and the locking nut into one piece to eliminate the potential structural weaknesses.…”
Section: Introductionmentioning
confidence: 99%